Densely Interconnected Porous BN Frameworks for Multifunctional and Isotropically Thermoconductive Polymer Composites. (3rd June 2018) - Xue, Yanming; Zhou, Xin; Zhan, Tianzhuo; Jiang, Baozhen; Guo, Quansheng; Fu, Xiuwei; Shimamura, Kiyoshi; Xu, Yibin; Mori, Takao; Dai, Pengcheng; Bando, Yoshio; Tang, Chengchun; et al.
Abstract: Ideal materials for modern electronics packaging should be highly thermoconductive. This may be achieved through designing multifunctional polymer composites. Such composites may generally be achieved via effective embedment of functional inorganic fillers into desirable polymeric bodies. Herein, two types of high‐performance 3D h ‐BN porous frameworks (3D‐BN), namely, h ‐BN nanorod‐assembled networks and nanosheet‐interconnected frameworks, are successfully created via an in situ carbothermal reduction chemical vapor deposition substitution reaction using carbon‐based nanorod‐interconnected networks as templates. These 3D‐BN porous materials with densely interlinked frameworks, excellent mechanical robustness and integrity, highly isotropous and multiple heat transfer paths, enable reliable fabrications of diverse 3D‐BN/polymer porous composites. The composites exhibit combinatorial multifunctional properties, such as excellent mechanical strength, light weight, ultralow coefficient of thermal expansion, highly isotropic thermal conductivities (≈26–51 multiples of pristine polymers), relatively low dielectric constants and super‐low dielectric losses, and high resistance to softening at elevated temperatures. In addition, the regarded 3D‐BN frameworks are easily recycled from their polymer composites, and may be reliably reutilized for multifunctional reuse. Thus, these materials should be valuable for new‐era advanced electronic packaging and related applications. Abstract : New types of porous BN frameworks, namely, high‐density BN nanorod‐interlinked and nanosheet‐interconnected networks, offer the possibility to create a series of multifunctional and isotropically thermoconductive porous polymer composites. The composites reveal outstanding isotropic thermal conductivities, and valuable multifunctions, including light weight, ultralow coefficient of thermal expansion, perfect dielectric properties, high resistance to softening at elevated temperatures, and easy recycling.